Structure Meets Society: Psychosocial Predictors of Structural Convergence in Multilingual Border Communities - Hanifah, Anisah Mutiara Zahra (Indonesian Scientific Publication, 2024)
This study investigates the role of psychosocial perception particularly prestige, social proximity, and identity in shaping structural convergence in multilingual contact zones. Focusing on four language pairs from Southeast Asia and Latin America, the research applies a dual-index model combining the Structural Convergence Index (SCI) and Psychosocial Index (PI) to evaluate the relationship between linguistic similarity and social perception. Structural features were extracted from typological databases (WALS, Grambank, PHOIBLE), while perception data were gathered via surveys measuring intergroup attitudes and identity alignment. Quantitative analysis revealed a strong positive correlation (r = 0.78) between SCI and PI scores, indicating that communities with higher perceived social proximity and shared prestige norms exhibited greater grammatical convergence. The study also identified domain-based variation, with convergence most pronounced in institutional contexts (e.g., schools, administration). In contrast, resistance to convergence particularly in the Fronterizo–Spanish case highlighted the impact of identity boundaries and sociopolitical ideologies. These findings support emerging models that treat language convergence as both a structural and socially mediated process. The SCI+PI model contributes a replicable and scalable method for assessing contact-induced change, advancing theoretical and methodological frontiers in contact linguistics. The results underscore that convergence is not only a linguistic outcome but also a reflection of social alignment, identity dynamics, and intergroup perceptions.